PELAKSANAAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (Corporate Social Responsibility) SEBAGAI SALAH SATU INSTRUMEN DALAM PEMBANGUNAN DAERAH - Busyra Azheri (Universitas Widya Gama Malang, 2019)
Given the limited funds of regional development, it is expected that CSR activities can be usedas an instrument in the regional development. This requires commitment from both parties forcorporate and government to formulate a clear policy, in accordance with the competenciesthey possess. So that CSR is not only beneficial to the corporation but also felt by the peopleand government in regional development.